Cognitive, emotional, and behavioral responses to interability communication styles in the workplace: Perspectives of people with disabilities - Byrd, Gabrielle A.; Zhang, Yan Bing (Communication monographs, 2023)
This experimental study, extending the communication accommodation theory and the Communication Predicament of Disability Model, examined people with disabilities' perceptions of four manipulated communication styles and tested the effects on their cognitive, emotional, and behavioral responses. Results revealed that participants in the integrative talk condition judged the coworker as the most competent and satisfying and had the least anxiety, followed by a relational talk, dismissive talk, and directive talk. Additionally, integrative talk resulted in the least internalized stigma and the highest likelihood of participants using accommodative response strategies, such as problem-solving and obliging. Furthermore, results revealed indirect effects of the communication styles on communication competence, satisfaction, stigma, and response strategies through communication anxiety.